2021
DOI: 10.3390/children8080634
|View full text |Cite
|
Sign up to set email alerts
|

Independent Risk Factors for RBC Transfusion in Children Undergoing Surgery. Analysis of 14,248 Cases at a German University Hospital

Abstract: Background: paediatric patients are vulnerable to blood loss and even a small loss of blood can be associated with severe shock. In emergency situations, a red blood cell (RBC) transfusion may become unavoidable, although it is associated with various risks. The aim of this trial was to identify independent risk factors for perioperative RBC transfusion in children undergoing surgery. Methods: to identify independent risk factors for perioperative RBC transfusion in children undergoing surgery and to access RB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The number of investigated paediatric patients in our study is low; however, similar to adult patients, pre-operative anaemia in paediatric patients is independently associated with an increased risk for postoperative complications [19] and mortality [20]. An analysis of > 14,000 surgical paediatric patients demonstrated that 10.1% receive blood transfusions and that pre-operative anaemia is an independent predictor for transfusion in these patients (p < 0.001; OR = 15.10 with pre-operative anaemia and OR = 2.40 without pre-operative anaemia) [21]. Therefore, there is also an urgent need to provide pre-operative anaemia management for the paediatric patient population [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…The number of investigated paediatric patients in our study is low; however, similar to adult patients, pre-operative anaemia in paediatric patients is independently associated with an increased risk for postoperative complications [19] and mortality [20]. An analysis of > 14,000 surgical paediatric patients demonstrated that 10.1% receive blood transfusions and that pre-operative anaemia is an independent predictor for transfusion in these patients (p < 0.001; OR = 15.10 with pre-operative anaemia and OR = 2.40 without pre-operative anaemia) [21]. Therefore, there is also an urgent need to provide pre-operative anaemia management for the paediatric patient population [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Prompt and sufficient allogeneic blood product transfusion is often necessary to restore the oxygen transport capacity, maintain tissue oxygenation, maintain hemodynamics, and avoid cardiovascular failure. However, the efficacy and safety of blood transfusion remain concerns [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of minimally invasive surgery are well-known and have been reported multiple times in medical literature. The most important benefits include: faster recovery and return to everyday activities, less pain, a shorter hospital stay, fewer complications and better cosmetic effects [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
mentioning
confidence: 99%